PEMBERIAN EDUKASI TENTANG TRAINING OF TRAINER TEKNIK AKUPRESSUR KEPADA SISWA/SISWI SMA NEGERI 1 GADING REJO - Haqiqi, Faisal; Evelyne Septadilla; Niken Fitria Maya; Anisa Dwi Kartika; Rendra Orienta; Lira Budi Utami; Dinda Nurul Sari; Khalista Febiyanti; Elen Dwika Famela; Suci Choirunisa; Riska Novita; Sugiarto Sugiarto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Introduction: Acupressure is a widely used complementary therapy for managing minor health complaints without medication. However, students’ understanding of proper and safe acupressure techniques remains limited. Structured education is needed to improve their knowledge and skills in applying acupressure correctly. Objective: This community service activity aims to provide education and Training of Trainers (ToT) on acupressure techniques to students of SMA Negeri 1 Gading Rejo, enabling them to understand the concepts, benefits, and proper application of acupressure for relieving minor health problems independently. Method: The activity was conducted with 36 eleventh-grade students through interactive lectures, audiovisual media, demonstrations, hands-on practice, simulations, role play, discussions, Q&A sessions, and pre–post tests to measure knowledge improvement. The material included the definition, purpose, benefits, and techniques of acupressure for several conditions such as cough and cold, loss of appetite, menstrual pain, itching and hives, stress, insomnia, and headaches. Result: The program resulted in a significant improvement in students’ knowledge. Before the education, 90% of participants were categorized as having low knowledge. After the session, 50% reached the good category, 48% the sufficient category, and only 2% remained in the low category. Students were also active and cooperative throughout the activity and demonstrated the ability to perform acupressure techniques correctly after guided practice. Conclusion: Acupressure education using the ToT method proved effective in enhancing students’ knowledge and skills. Participants gained a better understanding that acupressure is a safe, practical, and low-risk complementary therapy for managing minor health complaints.